Evaluation of Efficacies of Some Insecticides against Major Insect Pests of Brinjal and Cabbage in Mid Hills of Meghalaya - Patra, Sandip; Dhamala, Sakil; Akoijam, Romila; Baiswar, Pankaj (International Journal of Bio-resource and Stress Management, 2021)
The experiments were conducted at ICAR Research Complex for North Eastern Hill Region, Umiam, Meghalaya, India to evaluate of some insecticides against major insect pests of brinjal and cabbage under field condition. All treatments viz. indoxacarb 14.5 SC (75 and 150 g a.i. ha-1), chlorfenapyr 10 SC (100 and 200 g a.i. ha-1), chlorpyrifos 20EC (200 and 400 g a.i. ha-1) and control (water spray) were applied thrice in brinjal and twice in cabbage at 15 days intervals. Shoot infestation in brinjal was counted from randomly selected five tagged plants from each replication before spray and on 7 and 14 days after application of insecticides. Fruits infestations were counted during harvesting only. In cabbage, larval population was counted from five randomly selected tagged plants from each replication on 1 day before and on 1, 3, 7, 14 days of each spray. Results revealed that the mean shoot infestation of brinjal was lowest in indoxacarb at double the recommended dose (4.82%) followed by indoxacarb at recommended dose (6.65%) with 80.19 and 72.66% reduction respectively over control check. The lowest brinjal fruit infestation (8.25%) also recorded at double the recommended dose of indoxacarb followed recommended dose (11.48%) of same insecticide. In cabbage, pooled of two years results revealed that indoxacarb @ 150 g a.i. ha-1 was very effective treatment with lowest number of larvae (0.98 larvae plant-1) followed by indoxacarb @ 75 g a.i. ha-1 (2.21 larvae plant-1) with higher marketable yield at both these treatments.